Validity of dynamical analysis to characterize heart rate and oxygen consumption during effort tests - Mongin, D.; Chabert, C.; Uribe Caparros, A.; Collado, A.; Hermand, E.; Hue, O.; Alvero Cruz, J. R.; Courvoisier, D. S. (Scientific Reports, 2020)
Performance is usually assessed by simple indices stemming from cardiac and respiratory data measured during graded exercise test. The goal of this study is to characterize the indices produced by a dynamical analysis of HR and VO2 for different effort test protocols, and to estimate the construct validity of these new dynamical indices by testing their links with their standard counterparts. Therefore, two groups of 32 and 14 athletes from two different cohorts performed two different graded exercise testing before and after a period of training or deconditioning. Heart rate (HR) and oxygen consumption (VO2) were measured. The new dynamical indices were the value without effort, the characteristic time and the amplitude (gain) of the HR and VO2 response to the effort. The gain of HR was moderately to strongly associated with other performance indices, while the gain for VO2 increased with training and decreased with deconditioning with an effect size slightly higher than VO2 max. Dynamical analysis performed on the first 2/3 of the effort tests showed similar patterns than the analysis of the entire effort tests, which could be useful to assess individuals who cannot perform full effort tests. In conclusion, the dynamical analysis of HR and VO2 obtained during effort test, especially through the estimation of the gain, provides a good characterization of physical performance, robust to less stringent effort test conditions.